Carles Salvador i la infraestructura cultural valencianista - Blasco, Ricard (Caplletra. Revista Internacional de Filologia, 2015)
This study analyzes how Salvador, as founder and collaborator, participated in various Valencian cultural institutions of his time: the Societat Castellonenca de Cultura, the Associació Protectora de l’Ensenyança Valenciana, the publications Taula de Lletres Valencianes and El Camí, Proa, Lo Rat-Penat, the Institut d’Estudis Valencians, and the Centre de Cultura Valenciana, among others.